2013
DOI: 10.1186/1471-2474-14-154
|View full text |Cite
|
Sign up to set email alerts
|

In vivo wear performance of highly cross-linked polyethylene vs. yttria stabilized zirconia and alumina stabilized zirconia at a mean seven-year follow-up

Abstract: BackgroundZirconia was introduced as an alternative to alumina for use in the femoral head. The yttria stabilized zirconia material was improved by adding alumina. We evaluated highly cross-linked polyethylene wear performance of zirconia in total hip arthroplasty. The hypothesis was that alumina stabilized zirconia could decrease highly cross-linked polyethylene wear.MethodsHighly cross-linked polyethylene wear was measured with a computerized method (PolyWare) in 91 hips. The steady-state wear rates were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Yttria-stabilized zirconia undergoes phase transformation in vivo [13,20], and was reported to cause increased wear of conventional polyethylene [25,26]. We expected a reduction in polyethylene wear when we used the alumina-stabilized zirconia heads, but this was not significant in this study.…”
Section: Accepted Manuscriptmentioning
confidence: 57%
See 2 more Smart Citations
“…Yttria-stabilized zirconia undergoes phase transformation in vivo [13,20], and was reported to cause increased wear of conventional polyethylene [25,26]. We expected a reduction in polyethylene wear when we used the alumina-stabilized zirconia heads, but this was not significant in this study.…”
Section: Accepted Manuscriptmentioning
confidence: 57%
“…The wear rates revealed in this study and other studies are similar. In particular, Hasegawa and Sudo [13] analyzed 91 hips of the Q hip system, in which the same highly cross-linked polyethylene and 26-mm zirconia heads were used, and reported a similar steady-state wear rate (0.02 mm/year).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to advanced densification technologies, there are other processing routes, such as the incorporation of reinforcing agents in different forms, such as whiskers, fibers and platelets [ 236 , 250 , 251 , 252 , 253 , 254 , 255 ]. Various reports [ 256 ] on the alumina (Al 2 O 3 ) and titania (TiO 2 ) composites with HAp have been done.…”
Section: Discussion On Dense Hydroxyapatitesmentioning
confidence: 99%
“…Previous studies reported that the steady-state wear rate of annealed HXLPE (Excellink; Kyocera) was 0.017 to 0.02 mm/year at 7 to 13-year. [15][16][17] The steady-state wear rate of remelted HXLPE in previous studies was 0 to 0.042 mm/year at 11 to 15-year (Longevity;…”
Section: Discussionmentioning
confidence: 99%